Humanism in Writing of R. K. Narayan Novels: Exploring Various Aspects of Humanism in R. K. Narayan's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Narayan has a tremendous combination of moving perspectives in him to check accomplishment in his objective. In the event that a peruser takes up Narayan‟s works, the main thing that hits the eye is their colossal assortment. He has composed on each possible subject among paradise and earth. He picks certain snapshots of most extreme significance in the lives of his characters, and afterward investigates those minutes with care.